Alteration of interleukin-10-producing Type 1 regulatory cells in autoimmune diseases. Issue 4 (July 2022) - Gregori, Silvia; Amodio, Giada; Passerini, Laura; Santoni de Sio, Francesca Romana
Abstract : Purpose of review: This review highlights findings describing the role of interleukin (IL)-10-producing Type 1 regulatory T (Tr1) cells in controlling autoimmune diseases and possible approaches to restore their function and number. Recent findings: Reduced frequency and/or function of cell subsets playing a role in Tr1 cell induction (e.g., DC-10 and Bregs), was found in patients with autoimmunity and may impact on Tr1 cell frequency. Summary: IL-10 is a pleiotropic cytokine with fundamental anti-inflammatory functions acting as negative regulator of immune responses. IL-10 is critically involved in the induction and functions of Tr1 cells, a subset of memory CD4 + T cells induced in the periphery to suppress immune responses to a variety of antigens (Ags), including self-, allogeneic, and dietary Ags. Alterations in IL-10-related pathways and/or in the frequency and activities of Tr1 cells have been associated to several autoimmune diseases. We will give an overview of the alterations of IL-10 and IL-10-producing Tr1 cells in Multiple Sclerosis, Type 1 Diabetes, and Celiac Disease, in which similarities in the role of these tolerogenic mechanisms are present. Current and future approaches to overcome Tr1 cell defects and restore tolerance in these diseases will also be discussed.